Physicochemical and Functional Characteristics of Analog Rice Made from Local Cassava and Red Kidney Bean - Paulus Risan Funan Lalong; Maria Novalina Naben; Joanivita P.G. Soru; Eufrasia R.A. Lengur; Maximus M. Taek (The University of Lampung, 2025)
Nuabosi cassavas and Inerie red kidney beans are local foods from East Nusa Tenggara whose processing is relatively limited, but they have the potential to be developed into analog rice. This study aims to determine the effects of various compositions of Nuabosi cassava flour and Inerie red kidney bean flour on the characteristics of the produced analog rice. The procedure was conducted in three main stages: the preparation of cassava flour and red beans, formulation and production, and analysis. Various compositions of Nuabosi cassavas flour and Inerie red kidney beans were used: 98:0 (A); 88:10 (B); 83:15 (C); 78:20 (D); 73:25 (E). The data were analyzed by ANOVA, followed by DMRT at a 5% significance level. The results of the study showed, analog rice sample D (78% cassavas flour: 20% red kidney beans flour) has the best physicochemical and antioxidant activity characteristics of all samples. Furthermore, the sensory analysis results showed that most panelists had started to like the aroma, taste, and texture of analog rice made from 78% cassavas flour and 20% red kidney beans flour. Analog rice made from Nuabosi cassavas and Inerie red kidney beans has the potential to be developed as a functional food. Keywords: Kriging interpolation; MSFI; paddy field; soil fertility index, soil mapping.